LAPORAN KEUANGAN ARUS KAS DALAM PANDANGAN SYARIAH (STUDI PADA PT. BANK PANIN DUBAI SYARIAH, Tbk) - Khodijah, Ina; Afriani, Raden Irna (Aksara Public, 2019)
The purpose of this study is to formulate a form of cash flow statement sharia intact. The benefits of research with formulated cash flow statement sharia expected were: first, accounting sharia which until recently remained at the level of philosophical theoretical can be implemented in the field. Second, to contribute to the practical accountant do his practice according to Islamic values and goals syariah; the third gives empirical evidence that actual Muslims still do accounting activity appropriate syariah that can serve as a source of financial reports developing syariah; all four contributed constructively in the preparation of the financial accounting standards for companies outside of Sharia Banking. The results in this research is in the operating activities of PT. Bank Panin Dubai Syariah,Tbk if seen from the receipt of the cash flow ketundukkan is in compliance with Sharia cash flow statement the cash flow out yet for ketundukkan is still not listed. While the cash flow from investments rather than cash flow comes from the acceptance of the transaction but rather of ketundukkan creativity. Whereas the funding of the activity is in compliance with Sharia cash flow statement but still need for conformity. And for great deals in substance may have already done but in its cash flow statement is not in the list. Because of its form of Sharia cash flow statement for Banking still need further elaboration. Also realized that the financial statements of the above sharia still has many limitations. Conceptually the financial statements still have constraints to the depth of the substance.